KOMPETENSI PROFESIONAL GURU BIMBINGAN KONSELING DALAM PEMECAHAN MASALAH BELAJAR SISWA DI MAN RUKOH BANDA ACEH - Hazrullah Hazrullah; Furqan Furqan (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2018)
Competency is a standard of ability required to describe both qualitative and quantitative qualifications of a person. It also underlies the execution of professional duties or technical skills. A person is declared competent in a particular area if he masters the skills related to his field of work. To carry out his duties, a counseling teacher at MAN Rukoh Banda Aceh must perform his job professionally so that the counseling guidance process works well. This research discusses the professional competencies that must be owned by a counseling teacher to solve the learning problems experienced by students at MAN Rukoh Banda Aceh. This research uses a descriptive qualitative method. The data is obtained from observation, interview, and documentation. The results showed that counseling teachers at MAN Rukoh have a relevant educational background. Eventually, they have professionally done their work and also responsibly solve student's problems. The counseling teachers at MAN Rukoh Banda Aceh provide individual services for students so that their learning problems can be solved well.